Finite element analysis theory and application with ANSYS - Moaveni, Saeed (Prentice Hall, 1999)
"In recent years, the use of finite element analysis as a design tool has grown rapidly. Easy to use comprehensive packages such as ANSYS, a general-purpose finite element computer program, have become common tools in the hands of engineers. This book is written to assist engineering students and practicing engineers new to the field of finite element modeling, to gain a clear understanding of the fundamentals of finite element modeling. The text offers insight into the theoretical aspects of finite element analysis and great care has been exercised to avoid overwhelming students with theory. Yet, enough theoretical background is offered to allow individuals to use ANSYS intelligently and effectively. ANSYS is an integral part of this text."--Jacket.